Media Ownership, Differential Coverage, and Effects on Public Attitudes : The Case of News Coverage of Labour Unions - KNEAFSEY, LIAM MICHAEL (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2018)
This dissertation examines the relationship between media ownership structures, the influence ownership has on news content and the effects of differential coverage on citizens who consume this content. It examines the news coverage of labour unions as a case study of how this causal mechanism operates. The study uses a combination of quantitative text analysis, laboratory and survey experiments, repeated-measures survey designs, and qualitative interview evidence to address the components of the causal mechanism sequentially. Chapter 2 focuses on a quasi-experimental design where the unusual circumstances of a newspaper takeover are leveraged to test whether a change in ownership structure causes a change in the tone of coverage of unions as the incentive and ability to control journalists and editors shifts. The chapter utilises newly collected archival newspaper data, dictionary-based text analysis, and a combination of treatment tests, changepoint analysis, and difference-in-difference methods to establish the causal effect. Chapter 3 explores the effects of differential framing of a contemporary news story regarding the regulation, activities, and role of labour unions drawn from commercial media organisations with different ownership structures. The chapter tests for effects of differential news content on attitudes through a combination of traditional laboratory and state-of-the-art online survey experiments. Chapter 4 leverages the salience of the 1984-85 UK Miners? Strike to explore whether and how the news coverage of the strike by differentially owned outlets affected citizens? broader attitudes to unions. The chapter combines content analysis of newly collected archival data from a number of major UK newspapers and the BBC with survey analysis of repeated measures of attitudes to identify how news coverage shaped opinion during the strike. Chapter 5 uses semi-structured qualitative interviews with editors and journalists drawn from media organisations with a variety of ownership structures to examine the methods by which owners control the news coverage their outlets produce. The chapter allows for an investigation of patterns of direct and indirect influence and demonstrates how the hypothesised causal effects discussed in earlier chapters operate in practice.
APPROVED
Keywords: media ownership; experiments; text analysis; news media; political communication; political psychology; political economy; unions